Sosialisasi Asuransi Sebagai Alat Edukasi Keuangan: Tantangan dan Peluang di Indonesia - Ardiansari, Lia; Anjarwati, Ani; Qomariyah, Ryzca Siti; Devi, Nourma Ulva Kumala; Arista, Hermin; Wati, Dian Anisa Rokhmah (Jurnal SOLMA, 2025)
Background: Socialization of insurance as a financial education tool is one of the important efforts in improving financial literacy of the Indonesian people. In the context of community service, this activity aims to help the community understand the importance of risk management and strengthen the financial foundations of individuals and families. Methods: The methods used include counseling, interactive discussions, and case study simulations involving collaboration between educational institutions and local communities. Results: Overall, this activity not only succeeded in increasing participants' knowledge about insurance with an average score of 1.40 points or around 26.31%, but also opened up new opportunities for them to utilize insurance as a risk management tool and source of income. This activity can be optimized through community-based programs and integration of financial literacy into the formal education curriculum. Conclusions: In the context of community service, education about insurance not only helps the community understand the importance of risk management, but also strengthens the financial foundation of individuals and families. Collaboration with educational institutions and local communities can also increase community acceptance of insurance education. Counseling programs that focus on the specific needs of the community and the integration of financial literacy into the formal education curriculum are strategic steps that can optimize the positive impact of insurance socialization.